Penerapan Metode Promethee dengan Entropy Dalam Pengambilan Keputusan untuk Menentukan Siswa Berprestasi - Majdi, Abdul Hamid (Jurnal Pendidikan Informatika (EDUMATIC), 2017)
Realizing competitiveness, quality and achievement schools is one of the forms of mission and vision that is applied in schools, especially in students. To realize that desire every school needs to evaluate, further improve its services both on teaching techniques, assessment, and quality assurance in order to make schools that are competitive, quality and achievers. In this case the homeroom is confronted with a problem of the quality assessment of each student according to the criteria desired by the school, and become the burden of the homeroom because of the many choices in determining which ones are more prioritized and must be compared so that they cannot be timely in their completion. To identify the problems faced by the school, especially the homeroom teacher is used is a promethee approach which is one method of determining the order or priority in multicriteria analysis is very appropriate to use because the assumption of the dominance of the criteria used in promethee is the use of values in outrangking relationships. So that a solution or result of several alternatives is obtained to make a decision. The results of the ranking show that promethee I is based on the value of leaving flow and entering flow while Promethee II is based on the net flow value.